PROTECTIVE EFFECT OF NON-IRRADIATED AND Î“-IRRADIATED MANGO (MANGIFERA INDICA L.) JUICE AGAINST ETHANOL-INDUCED OXIDATIVE STRESS IN ALBINO RATS - Kondapalli Naresh; Sadineni Varakumar; Natava Rajesh; Variyar, Prasad Shekhar; Obulam Vijaya Sarathi Reddy (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The aim of this study is to explore the protective effect of non-irradiated and Î³-irradiated mango juice (NMJ and GMJ) against ethanolinduced hepatic and renal dysfunction in rats. Methods: A total of 36 male Wistar rats were selected and randomly divided into six groups of six animals each, and the treatment was given every day via orogastric tube for 30 days. Group I rats served as normal control group. Group II, III, IV, V, and VI rats received absolute ethanol, NMJ, GMJ, ethanol+NMJ, and ethanol+GMJ, respectively. At the end of experimental period, the animals were sacrificed, and serum was separated for liver and kidney markers analysis. The tissues (liver and kidney) were excised for histopathological changes and lipid peroxidation, enzymatic, and nonenzymatic antioxidants activities were estimated. Results: Ethanol treatment resulted in the depletion of superoxide dismutase, catalase, glutathione peroxidase, glutathione reductase, glutathione-stransferase activities, and reduced vitamin C and reduced glutathione content, higher level of malondialdehyde, increased activities of serum alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, gamma-glutamyl transpeptidase and elevated levels of serum urea, creatinine, uric acid causing malfunction of hepatic, and renal tissues, when compared to control rats. Mango juice (both NMJ and GMJ) co-treatment with ethanol ingested rats, were envisaged to possess significant antioxidant defense properties and help in the recovery of tissues from ethanol-induced oxidative damage. The results showed that degenerative changes in hepatic and renal cells of ethanolic groups were minimized by the administration of mango juice, as revealed by histopathological examination. Conclusion: The current findings suggest that treatment with mango juice reduces ethanol-induced oxidative stress, thereby protecting the hepatic and renal tissue from ethanol-induced damage. Keywords: Î³-irradiation, Mango juice, Ethanol, Oxidative stress, Antioxidant enzymes, Liver, Kidney.